2017
DOI: 10.1111/jopy.12359
|View full text |Cite
|
Sign up to set email alerts
|

The convergence and divergence of impulsivity facets in daily life

Abstract: These results generally support a four-factor model of multidimensional impulsivity with a general overall urgency factor instead of separate positive and negative urgency facets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
59
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 43 publications
8
59
0
3
Order By: Relevance
“…Participants in this study also endorsed low rates of substance use problems and self-harm/suicidal ideation at discharge, limiting the ability of our analyses to detect potential influences of positive urgency. Although closely correlated with negative urgency [4], positive urgency has also been identified as a correlate of specific symptoms and behaviors, such as bipolar disorder [12], problems with alcohol use [45], and risky sexual behavior [20]. Average scores on the Positive Urgency measures were lower than those for Negative Urgency in the present study; it is possible that positive urgency may be more relevant for treatment outcomes in these specific populations.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Participants in this study also endorsed low rates of substance use problems and self-harm/suicidal ideation at discharge, limiting the ability of our analyses to detect potential influences of positive urgency. Although closely correlated with negative urgency [4], positive urgency has also been identified as a correlate of specific symptoms and behaviors, such as bipolar disorder [12], problems with alcohol use [45], and risky sexual behavior [20]. Average scores on the Positive Urgency measures were lower than those for Negative Urgency in the present study; it is possible that positive urgency may be more relevant for treatment outcomes in these specific populations.…”
Section: Discussionmentioning
confidence: 57%
“…An important goal for future research will be to determine which aspects of treatment (if any) are related to decreases in this trait, and to evaluate specific mechanisms that help both negative and positive urgency to subside. For example, urgency is somewhat correlated with related constructs such as distress tolerance [47, 48], as well as with negative affect more broadly [4]. Difficulties tolerating distress also decrease during partial hospital treatment [49], so it is possible that improvements in urgency are mediated by improvements in distress tolerance or other similar mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While early models of emotion‐related impulsivity characterized a factor defined as negative urgency, the tendency to act impulsively in response to negative emotion (Whiteside & Lynam, ; Whiteside et al, ), later work identified a separable factor of positive urgency, the tendency to act impulsively in response to positive emotion (Cyders & Smith, ). More recently, factor analytic evidence suggests that these two factors have a common underlying core (Carver, Johnson, Joormann, Kim, & Nam, ; Sperry, Lynam, & Kwapil, ). Because tendencies to respond impulsively to heightened emotion occur across both positive and negative emotions (Cyders et al, ), heightened arousal, rather than valence, may be the trigger.…”
Section: Introductionmentioning
confidence: 99%